Strain engineering of two-dimensional materials for advanced electrocatalysts. (June 2021) - Xu, X.; Liang, T.; Kong, D.; Wang, B.; Zhi, L.
Abstract: Electrocatalysis is of great significance for the conversion and utilization of clean energy industrially. Along with the pursuing of highly efficiency and selectivity, an exploded number of catalysts have been designed, among which two-dimensional (2D) materials have attracted growing attention due to their outstanding physical and chemical properties. Recently, growing attention has been paid to strain engineering as it was reported to be able to modify the electronic structure, and thus, alter the catalytic activity of nanomaterials, including the 2D family; however, a summary of strain engineering effect of 2D materials on their electrocatalytic properties lacks to our knowledge. As such, we provide this review by discussing three aspects, including the strain engineering method, the influence of strain on the electronic structure of 2D materials, and its use and mechanism in electrocatalysis. This timely review aims to clarify the current development of this topic so as to promote the concern on such strained catalysts and bring the mechano-electrochemical concept into the view of this traditional field.